Neonatal repetitive needle pricking: Plasticity of the spinal nociceptive circuit and extended postoperative pain in later life. Issue 1 (23rd August 2012) - Knaepen, Liesbeth; Patijn, Jacob; van Kleef, Maarten; Mulder, Mark; Tibboel, Dick; Joosten, Elbert A.J.
Abstract Repetitive exposure of neonates to noxious events is inherent to their health status monitoring in neonatal intensive care units (NICU). Altered basal nociception in the absence of an injury in later life has been demonstrated in ex‐NICU children, but the impact on pain hypersensitivity following an injury in later life is unknown. Also, underlying mechanisms for such long‐term changes are relatively unknown. The objective of this study is to investigate acute and long‐term effects of neonatal repetitive painful skin‐breaking procedures on nociception and to investigate plasticity of the nociceptive circuit. The repetitive needle prick animal model was used in which neonatal rats received four needle pricks into the left hind paw per day during the first postnatal week and control animals received nonpainful tactile stimuli. Repetitive needle pricking during the first week of life induced acute hypersensitivity to mechanical stimuli. At the age of 8 weeks, increased duration of postoperative hypersensitivity to mechanical stimuli after ipsilateral hind paw incision was shown in needle prick animals. Basal nociception from 3 to 8 weeks of age was unaffected by neonatal repetitive needle pricking. Increased calcitonin gene‐related peptide expression was observed in the ipsilateral and contralateral lumbar spinal cord but not in the hind paw of needle prick animals at the age of 8 weeks. Innervation of tactile Aβ‐fibers in the spinal cord was not affected. Ourresults indicate both acute and long‐term effects of repetitive neonatal skin breaking procedures on nociception and long‐term plasticity of spinal but not peripheral innervation of nociceptive afferents. © 2012 Wiley Periodicals, Inc. Develop Neurobiol, 2013